Public Compliance in Land and Building Tax Payment in Kulo District, Sidenreng Rappang Regency - Citra Dwi Amaliah; Barisan; Irwan (Journal of Governance, Taxation and Auditing, 2026)
This study aims to analyze public compliance in Land and Building Tax (Pajak Bumi dan Bangunan/PBB) payment in Kulo District, Sidenreng Rappang Regency. The study is motivated by the decline in PBB revenue realization from 86.47% in 2022 to 83.59% in 2023 and 78.91% in 2024, indicating that taxpayer compliance has not been optimal. This study employed a qualitative descriptive approach based on the Slippery Slope Theory and the Theory of Planned Behavior. Data were collected through observation, interviews, and documentation involving government officials, taxpayers, and community leaders as informants. The findings indicate that public compliance in PBB payment remains suboptimal. This condition is influenced by the limited public understanding of payment procedures, insufficient socialization, administrative constraints related to tax objects, economic capacity, and public perceptions of tax benefits. In addition, the role of local government in socialization, service delivery, and supervision has not been fully effective in encouraging taxpayer compliance. This study concludes that PBB payment compliance is influenced by behavioral, administrative, and institutional factors. Therefore, improved socialization, better tax administration, strengthened public services, and increased public trust in local government are needed.